2015
DOI: 10.1016/j.enganabound.2015.04.005
|View full text |Cite
|
Sign up to set email alerts
|

A three-dimensional implementation of the boundary element and level set based structural optimisation

Abstract: a b s t r a c tThis paper presents a three-dimensional structural optimisation approach based on the boundary element and level set methods. The structural geometry is implicitly represented with the level set method, which evolves an initial structural model towards an optimal configuration using an evolutionary structural optimisation approach. The boundary movements in the three-dimensional level set based optimisation method allow automatic hole nucleation through the intersection of two surfaces moving to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…The stress based hole insertion criterion is further investigated for a possible correlation with a topological derivative based hole insertion mechanism in [23]. The BEM and LSM based evolutionary optimisation method is further extended for the solution of three-dimensional problems in [24].…”
Section: Introductionmentioning
confidence: 99%
“…The stress based hole insertion criterion is further investigated for a possible correlation with a topological derivative based hole insertion mechanism in [23]. The BEM and LSM based evolutionary optimisation method is further extended for the solution of three-dimensional problems in [24].…”
Section: Introductionmentioning
confidence: 99%
“…The three-dimensional BEM and LSM based BESO approach for a specific strain energy objective function without a constant volume implementation has been studied in the authors previous work as reported in [12]. Where it has been shown that the proposed approach can be easily extended to three-dimensions.…”
Section: Terminate If |Vmentioning
confidence: 99%
“…• the boundary element method (BEM) based boundary only discretisation The reduction of problem dimensionality with the use of BEM based body conforming mapping is very attractive as compared to the FEM based domain discretisation. In the literature of structural optimisation, researchers combined the BEM with the LSM for the solution of optimisation problems in both two and three-dimensions, e.g, compliance minimisation [10,11,12,13], sound scattering [14,15], heat conduction [16], etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since Laplacian smoothing is simple, general and well-understood, it is often the technique of choice when a smoothing or noise suppression algorithm needs to be incorporated into a general mesh processing framework [10], or into a more complex algorithm, as for example the machine learning algorithm for surface reconstruction in [1], or the Boundary Element Method based evolutionary structural optimization in [17].…”
Section: Introductionmentioning
confidence: 99%